2009
DOI: 10.1211/jpp/61.04.0002
|View full text |Cite
|
Sign up to set email alerts
|

Phycocyanin liposomes for topical anti-inflammatory activity: in-vitro in-vivo studies

Abstract: The results showed that C-PC can be successfully used as an anti-inflammatory drug and that liposomal encapsulation is effective in improving its anti-inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
(41 reference statements)
0
13
0
1
Order By: Relevance
“…The antioxidant and antiinflammatory properties of phycocyanin were first reported in 1998 [80, 81] and confirmed by numerous studies thereafter [20, 8292]. Phycocyanin has the ability to scavenge free radicals, including alkoxyl, hydroxyl and peroxyl radicals.…”
Section: Mechanism Of Actionmentioning
confidence: 95%
See 1 more Smart Citation
“…The antioxidant and antiinflammatory properties of phycocyanin were first reported in 1998 [80, 81] and confirmed by numerous studies thereafter [20, 8292]. Phycocyanin has the ability to scavenge free radicals, including alkoxyl, hydroxyl and peroxyl radicals.…”
Section: Mechanism Of Actionmentioning
confidence: 95%
“…Phycocyanin has the ability to scavenge free radicals, including alkoxyl, hydroxyl and peroxyl radicals. It also decreases nitrite production, suppresses inducible nitric oxide synthase (iNOS) expression, and inhibits liver microsomal lipid peroxidation [20, 8092]. Using recombinant technology, phycocyanin protein has been expressed and the antioxidant activity is also demonstrated with the recombinant phycocyanin protein [93, 94].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…(+)‐Catechin and (–)‐epicatechin are also the building blocks of most proanthocyanins (oligomers or polymers of flavan‐3‐ol units) [14] . Besides the classical biological and pharmacological activities described for several flavonoids, such as anti‐inflammatory and antioxidant properties, [15,16] many studies have reported their effects on the central nervous system (CNS) as analgesics, anxiolytics and sedatives [16,17] …”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Here, we are giving some reference to support above statements. Fadda et al [36] developed phycocyanin loaded liposomes by the film hydration techniques. They reported that phycocyanin (C-Pc) loaded liposomes were adsorbed on stratum corneum and accumulated C-Pc on stratum corneum.…”
Section: Liposomes As Carrier For Dermal Drug Delivery Systemsmentioning
confidence: 99%